The Meaning of Life in the Elderly: The Role of Logotherapy in Reducing Hopelessness - Indah Purnama Sari; Sri Rahmawati Agus; Alif Muarifah (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2026)
Aging naturally triggers physical and psychological changes that often lead to hopelessness, characterized by a loss of hope and control over the future. This study aims to examine the effectiveness of logotherapy in reducing hopelessness by strengthening the meaning of life among elderly women. Using a quantitative pre-test and post-test design, 33 participants aged 57–82 years at Griya Lansia X Yogyakarta were assessed using the General Hopelessness Scale. Data analysis using the Paired Sample t-Test showed a significant difference between pre-test and post-test scores (t = 10.33, p < .001). These findings prove that logotherapy is effective in helping the elderly rediscover life goals and psychological well-being. This intervention serves as a strategic protective measure for vulnerable elderly groups to restore their social roles and daily life satisfaction.